Regional pattern of the molecular types of Cryptococcus neoformans and Cryptococcus gattii in Brazil - Luciana Trilles; Márcia dos Santos Lazéra; Bodo Wanke; Raquel Vasconcelos Oliveira; Gláucia Gonçalves Barbosa; Marília Martins Nishikawa; Bernardina Penarrieta Morales; Wieland Meyer (Memorias do Instituto Oswaldo Cruz, 2008)
The molecular types of 443 Brazilian isolates of Cryptococcus neoformans and Cryptococcus gattii were analyzed to determine their geographic distribution within Brazil and their underlying host conditions. The following data, imported from previous epidemiological studies as well as two culture collections, were analyzed for: place of isolation, source (clinical or environmental), host risk factors, species, serotype, mating type, and molecular type. Molecular typing by PCR-fingerprinting using primers for the minisatellite-specific core sequence of the wild-type phage M13 or microsatellites [(GACA)4, (GTG)5], restriction fragment length polymorphism of URA5 gene analysis, and/or amplified fragment length polymorphism (AFLP) identified eight major genotypes: VNI/AFLP1, VNII/AFLP1A, VNIII/AFLP2, and VNIV/AFLP3 for C. neoformans, and VGI/AFLP4, VGII/AFLP6, VGIII/AFLP5, and VGIV/AFLP7 for C. gattii. The most common molecular type found in Brazil was VNI (64%), followed by VGII (21%), VNII (5%), VGIII (4%), VGI and VNIV (3% each), and VNIII (< 1%). Primary cryptococcosis caused by the molecular type VGII (serotype B, MAT) prevails in immunocompetent hosts in the North and Northeast regions, disclosing an endemic regional pattern for this specific molecular type in the Northern Brazil.